Forensic Accounting Techniques and Performance of Public Sectors in Nigeria - Onyebuchukwu Orji (Ph.D) (International Journal of Economics and Financial Management, 2026)
The paper examined the effect of Forensic Accounting Techniques on the Performance of public sector. Forensic accounting, the independent variable was measured using litigation support service, mediation, detection and deterrence skill, while public sector performance, the dependent variable was proxy using quality service delivery. Primary data collected through structured questionnaire was used for the study. The population of the study consists of 182 staff of finance and accounts, treasury and internal revenue service departments of the Rivers State Ministry of Finance out of which a sample size of 125 was drawn using Taro Yamen’s formula, the data collected were analyzed using the Pearson’s product Moment Correlation (PPMC) technique. The findings revealed that: Litigation support service, mediation, detection and deterrence skill does significantly improve, contribute and enhance the quality of service delivery in Nigeria public sector. It was noted from the findings that all variables for for